2019
DOI: 10.1001/jamaophthalmol.2018.5398
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Macular Visual Field Measurements With Glaucoma Staging Systems

Abstract: IMPORTANCE Macular function is important for daily activities but is underestimated when tested with 24-2 visual fields, which are often used to classify glaucoma severity.OBJECTIVE To test the hypothesis that current glaucoma staging systems underestimate glaucoma severity by not detecting macular damage. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional study was carried out in a glaucoma referral practice. The eyes of participants with manifest glaucoma and 24-2 mean deviation (MD) better than −6 dB wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 35 publications
0
22
0
3
Order By: Relevance
“…21 and that in some grading systems, the presence of any central visual field defect may be regarded as advanced glaucoma, in the absence of significant mean deviation loss. 24…”
Section: Visual Field Testing and Data Extractionmentioning
confidence: 99%
“…21 and that in some grading systems, the presence of any central visual field defect may be regarded as advanced glaucoma, in the absence of significant mean deviation loss. 24…”
Section: Visual Field Testing and Data Extractionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Thus, it appears that the presence of central VF damage, irrespective of severity of the global VF damage, may have significant implications on disease staging. 41 In addition, our previous work has demonstrated that the presence of central VF damage is predictive of global VF progression independent of baseline 24-2 mean deviation. 42 Importantly, central VF damage has been associated with poor vision-related quality of life outcomes even in early glaucoma.…”
Section: Discussionmentioning
confidence: 95%
“…(30) . Esse número é notável pois muitos dos chamados "suspeitos de glaucoma" ou "glaucoma pré-perimétrico" podem de fato apresentar lesão macular que agora os classificaria como "glaucoma grave", conforme sistemas de classificação existentes (30)(31)(32) . Com metodologia semelhante, Park et al (12) anormalidades em até 36% dos olhos com defeitos maculares (27) (35) .…”
Section: Tabelasunclassified
“…Primeiro, conforme demonstrado por vários autores utilizando-se dados transversais (12,13,28) , incluindo-se estudos realizados por De Moraes e colaboradores que serviram de premissa para o presente estudo (8,11,26,27,31) , o uso exclusivo de perimetria acromática 24-2 e OCT de CFNR peripapilar pode levar a não detecção de dano funcional e estrutural na mácula. Por exemplo, De Moraes et al (31) demonstraram que a perimetria 24-2 pode não detectar lesão funcional e estrutural na mácula em até 70% dos pacientes considerados suspeitos de glaucoma ou portadores de glaucoma inicial. A detecção de dano funcional central nesses pacientes não só altera seu diagnóstico (de suspeito ou pré-perimétrico para glaucoma manifesto), como também os classifica como tendo defeito avançado (30) , com provável impacto em sua qualidade de vida (18)(19)(20) .…”
Section: Paradigma De Um Ensaio Clínico Randomizadounclassified
See 1 more Smart Citation